Simultaneous laparoscopic liver resection: a single-center experience - G. G. Akhaladze; E. N. Grebenkin; V. D. Chkhikvadze; U. S. Stanojević; S. V. Goncharov; V. A. Ragimov; R. V. Kolesnikov; A. A. Abramov (Alʹmanah Kliničeskoj Mediciny, 2018)
Background: About 15 to 25%  of colorectal cancer patients have synchronous liver metastasis at diagnosis. In the recent years, the strategy of simultaneous removal of colorectal cancer and liver metastases has been preferred. Development of minimally invasive technologies in abdominal and hepatopancreatobiliary surgery allows for active advance to fully laparoscopic approach to these types of interventions.Aim: Comparative analysis of simultaneous and isolated laparoscopic liver resections performed in the Department of Surgery, Russian Research Center of Roentgenoradiology (Moscow).Materials and methods: We have analyzed intra- and postoperative results of 29 laparoscopic procedures for metastatic liver disease. Group 1 included 14 patients who had undergone simultaneous laparoscopic primary tumor resection and laparoscopic liver resection for metastatic disease. Group 2 included 15 patients who had undergone isolated laparoscopic liver resection for metastatic lesions.Results: Mean (± SD) blood loss in the simultaneous and isolated procedures groups was 469 ± 176 and 408 ± 124  mL, respectively (p = 0.2), whereas the duration of surgeries was 296 ± 107  and 204 ± 82  min, respectively (p = 0.01). Conversion rate in the isolated resection group was higher (26% vs. 14%). This difference is to be explained by the learning curve in laparoscopic liver surgery. All liver resections in both groups were carried out in R0 mode. No deaths and significant complications were seen in any of the groups.Conclusion: The study demonstrated feasibility and safety of simultaneous, fully laparoscopic liver resections, including those for difficult localization of primary tumors and metastatic lesions.